Searching for the Optimal Relationships Between SIRGAS2000, South American Datum of 1969 and Corrego Alegre in Brazil - Oliveria, Leonardo C.; Santos, Marcelo C.; Nievinski, Felipe G.; Leandro, Rodrigo F.; Costa, Sonia M. A.; Santos, Marcos F.; Magna, Joao [UNESP]; Galo, Mauricio [UNESP]; Camargo, Paulo O. [UNESP]; Monico, Joao G. [UNESP]; Silva, Carlos U.; Maia, Tule B.; et al. (Springer, 2009)
Brazil has moved towards the adoption of a geocentric system, SIRGAS2000. With the adoption of this system, starting in 2005, a great demand has been created towards transforming the current data sets from the South American Datum of 1969 (SAD-69), in its two distinct realizations, and the Corrego Alegre frames into SIRGAS2000. The fact that these four frames will co-exist until 2014 creates positive and negative situations. Due to the distortion between those frames, the relationships among them cannot be well established with Helmert transformation parameters alone. To solve this problem, five Study Groups were created to look for the optimal relationships for coordinate transformation between those frames. The approaches being investigated to augment the parameter transformation are based on: Collocation, Delaunay, Regular grids (NTv2 and Sheppard method) and Neural Networks. The research is currently going on. This paper describes the current efforts towards defining the optimal relationships among these four frames, from the mathematical point-of-view. The work described in the paper has been carried out under the scope of the National Geospatial Framework Project (www.pign.org), sponsored by the Canadian International Development Agency.
Keywords: Reference frames; Coordinate transformations; Distortion modelling